Al amyloidosis with cardiac involvement: cardiotoxicity of aggregation prone peptides deriving from variable domains of immunoglobulin light chains. (25th November 2020) - Nikolaou, P.E; Nasi, G.I; Sulaiman, I; Spatharas, P; Kikionis, S; Efentakis, P; Ioannou, E; Roussis, V; Davidson, S.M; Terpos, E; Dimopoulos, M.A; Kastritis, E; et al.
Abstract: Background/Introduction: Light chain (AL) amyloidosis is an uncommon malignancy manifested by systemic extracellular deposition of immunoglobulin light chain fibrils. The cardiac phenotype is characterised by ventricular wall thickening and stands as the most prominent cause of morbidity and mortality. Although, it has been established that the circulating light chains directly impair cardiomyocyte function, the cytotoxic effect of specific amyloidogenic peptides that may appear due to excessive cleavage of light chains remains unspecified. Purpose: In the present work, we aimed to detect amyloidogenic "hot-spots" on the variable domains of light chains associated with cardiac AL amyloidosis (IGLV1-44 and IGLV3-01) or inferior outcomes (IGLV6-57) and define their cytotoxic effect in vitro. Methods: At first, we used the curated database ALBase and we performed a multiple sequence alignment of the IGLV1-44, IGLV3-01 and IGLV6-57 inputs that derived only from patients with AL amyloidosis. "Aggregation-prone" hot-spots in the conserved amino acid sequences were identified with the aid of AMYLPRED2, a tool which combines 11 independent computational methods and provides a consensus result of potent amyloidogenic regions. Five peptides were rationally selected and synthetically produced in order to be tested in vitro. The amyloidogenic properties of the peptides were evaluated with Transmission Electron Microscopy and Congo red staining, while the rate of fibril formation at lower concentrations was monitored with Thioflavin T and confirmed with Scanning Electron Microscopy. In order to assess the cytotoxic effect of the non-polymerized peptides, H9C2 cells were incubated with the peptides for 24 hours at 200μg/mL and 100μg/mL and cell death was determined by lactate dehydrogenase release assay. Results: Interestingly, sequence alignment on the variable domains of cardiac related light chains revealed the presence of several conserved domains in patients with AL amyloidosis. The chosen peptides were proven to be amyloidogenic suggesting that the variable domains share common amyloidogenic cores. Treatment of H9C2 cells with the peptides at 200μg/mL led to significant reduction in cell viability compared to vehicle treated cells (p<0.001). Two of the peptides deriving from the IGLV6-57 and IGLV3-01 significantly increased cell death at 100μg/mL (p<0.01 and p<0.001 respectively). During the 24h treatment the tested peptides comprised of soluble species and not amyloid fibrils suggesting that monomeric and oligomeric intermediates are highly toxic. Conclusion: We discovered five novel amyloidogenic prone regions of cardiac related variable domains that are associated with cellular toxicity and could be exploited for targeted therapeutic interventions. Funding Acknowledgement: Type of funding source: None